The effect of docosahexaenoic acid (DHA) supplementation on total antioxidant capacity (TAC), superoxide dismutase (SOD), and interleukin-6 levels in underweight pregnant women - Siahaan, Salmon Charles; Santoso, Budi; Ismayani, Kanti; Yuwono, Natalia; Aris, Mohd Aznan Md (Universitas Airlangga, 2024)
HIGHLIGHTS Underweight pregnant women face an imbalance in energy and protein intake. TAC, SOD, and IL6 with administration of DHA to pregnant women with chronic energy deficiency in the third trimester provide benefits. ABSTRACT Objective: Underweight pregnant women face oxidative stress and inflammation, increasing their risk of intrauterine growth restriction (IUGR) and preterm birth. This study investigated the effects of DHA supplementation on Total Antioxidant Capacity (TAC), Superoxide Dismutase (SOD), and Interleukin-6 (IL-6) in underweight pregnant women, along with the correlation between DHA and these markers. Materials and Methods: This experimental pre-test/post-test study focused on underweight pregnant women in the Made District, Surabaya, Indonesia. Eligible participants were in their second or third trimester, had a BMI below 18.5, and were taking DHA regularly. Exclusion criteria included early pregnancy (gestational age <14 weeks), BMI above 18.5, irregular DHA intake, and withdrawal from the study. The study was performed from July to December 2023, using non-probability sampling to select participants. Blood samples were collected before and after two months of DHA supplementation. Results: Following the intervention, TAC levels demonstrated a significant increase (p < 0.05). SOD levels also exhibited a significant difference (p <0.05), and IL-6 levels showed a significant change (p < 0.05). A strong and positive correlation (r = 0.718) was observed between the increased TAC and SOD levels. DHA influenced both TAC and IL-6, with a significant relationship between TAC and IL-6 (p < 0.01). Furthermore, elevated SOD levels were associated with a decrease in IL-6 levels (p < 0.01). The correlation coefficient value of 0.718 between changes in SOD and TAC indicated a robust positive correlation. Conclusion: The findings suggest that DHA supplementation in underweight pregnant women positively affects oxidative stress and inflammation markers, improving TAC, SOD, and IL-6 levels.